Hot-electron transfer in quantum-dot heterojunction films - Grimaldi, Gianluca; Crisp, Ryan; Ten Brinck, Stephanie; Zapata, Felipe; Van Ouwendorp, Michiko; Renaud, Nicolas; Kirkwood, Nicholas; Evers, Wiel H.; Kinge, Sachin; Infante, Ivan; Siebbeles, Laurens D. A.; Houtepen, Arjan J. (Nature Communications, 2018)
Thermalization losses limit the photon-to-power conversion of solar cells at the high-energy side of the solar spectrum, as electrons quickly lose their energy relaxing to the band edge. Hot-electron transfer could reduce these losses. Here, we demonstrate fast and efficient hot-electron transfer between lead selenide and cadmium selenide quantum dots assembled in a quantum-dot heterojunction solid. In this system, the energy structure of the absorber material and of the electron extracting material can be easily tuned via a variation of quantum-dot size, allowing us to tailor the energetics of the transfer process for device applications. The efficiency of the transfer process increases with excitation energy as a result of the more favorable competition between hot-electron transfer and electron cooling. The experimental picture is supported by time-domain density functional theory calculations, showing that electron density is transferred from lead selenide to cadmium selenide quantum dots on the sub-picosecond timescale.